Arterial Stiffness Is More Associated with Albuminuria than Decreased Glomerular Filtration Rate in Patients with Type 2 Diabetes Mellitus: The REBOUND Study - Jong Ho Kim; Sang Soo Kim; In Joo Kim; Bo Hyun Kim; Ja Young Park; Chang Won Lee; Ji Hye Suk; Sun Hae Shin; Sung Pyo Son; Min Chul Kim; Jun Hyeob Ahn; Kwang Jae Lee; et al. (Journal of Diabetes Research)
Aim. The aim of this study was to evaluate the association between arterial stiffness and albuminuria and glomerular filtration rate (GFR) in patients with type 2 diabetes mellitus. Methods. This multicenter cohort study analyzed 2613 patients with type 2 diabetes. Brachial-ankle pulse wave velocity (baPWV) was used as a noninvasive marker of arterial stiffness. Additionally, the patients were categorized into four groups according to their albumin-to-creatinine ratio (ACR, normoalbuminuria versus albuminuria) and estimated GFR (eGFR, <60 mL/min/1.73 m2 versus ≥60 mL/min/1.73 m2). Results. A univariate analysis revealed that maximal baPWV was significantly associated with both the ACR (r=0.297, P<0.001) and eGFR (r=−0.220, P<0.001). A multivariate analysis adjusted for significant clinical variables and eGFR showed that baPWV remained significantly correlated with the ACR (r=0.150, P<0.001). Also, baPWV was correlated positively with the ACR in patients with an eGFR ≥ 60 mL/min/1.73 m2 (r=0.146, P<0.001). However, baPWV was not correlated with eGFR after adjustment for significant clinical variables. Conclusions. The present findings indicate that arterial stiffness is more associated with albuminuria than a decrease in GFR in patients with type 2 diabetes mellitus.